THE EFFECT OF BOARD OF COMMISSIONERS, AUDIT COMMITTEE, COMPANY SIZE, AND CAPITAL STRUCTURE ON AGENCY COSTS: INDONESIA PERSPECTIVE - Deo Dio Du Simanjuntak; Judith T. Gallena Sinaga (UNIB Press, 2021)
This research was conducted to examine whether agency cost can be influenced by the board of commissioners, audit committee, company size, and capital structure. This seeks to contribute to the literature of factors influencing agency cost in Indonesia. Agency cost exists because of some assymetircal information and conflicts between principal and agent. The study used descriptive method of which purposive sampling method was used in sample selection. The samples were selected from the top 100 largest wealth-creators companies in 2019 in Indonesia. Using the wealth-creators companies as the samples makes this research a unique one. The classical assumption test was conducted to check the relationship between variables. Data gathered were analyzed and interpreted using multiple regression analysisof which t-test and F-test were considered. The study revealed that agency cost was simultaneously influenced by the board of commissioners, audit committee, company size, and capital structure. Partially, this study found that board of commissioners and company size have siginificant influence on agency cost, while audit committee and capital structure have no influence on agency cost. The findings indicate that there are several factors that influences agency cost. Thus, agency cost can be minimized by proper monitoring by the presence of board of commissioner; while company size and capital structure trigger agency costs.